2011
DOI: 10.3758/s13414-011-0210-y
|View full text |Cite
|
Sign up to set email alerts
|

Coherence masking protection for speech in children and adults

Abstract: In three experiments, we tested the hypothesis that children are more obliged than adults to fuse components of speech signals and asked whether the principle of harmonicity could explain the effect or whether it is, instead, due to children’s implementing speech-based mechanisms. Coherence masking protection (CMP) was used, which involves labeling a phonetically relevant formant (the target) presented in noise, either alone or in combination with a stable spectral band (the cosignal) that provides no addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 53 publications
(87 reference statements)
4
30
0
Order By: Relevance
“…An earlier study by the authors revealed greater CMP for children than adults, with more resistance to disruptions in harmonicity across spectral components [Nittrouer and Tarr (2011). Atten.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…An earlier study by the authors revealed greater CMP for children than adults, with more resistance to disruptions in harmonicity across spectral components [Nittrouer and Tarr (2011). Atten.…”
mentioning
confidence: 85%
“…From a different perspective, however, that earlier outcome might be described as revealing how strongly children are obliged to process speech signals as integrated spectral patterns: It is not so much that children benefited more than adults from the high-frequency cosignal as it is that children were disadvantaged when it was not present. Cohen's d's computed on CMP scores for adults and 5-yr-olds in Nittrouer and Tarr (2011) were 2.49 for the F1-only condition and 1.40 for the F1 þ cosignal condition, meaning that age-related differences were greater for the F1-only condition than for the F1 þ cosignal condition. Thus, it seems fair to suggest that children required the broad spectral pattern for judging vowel quality, whereas adults were able to make do with F1 alone, to some extent.…”
Section: A Phonetic Coherence In Children's Speech Perceptionmentioning
confidence: 96%
“…This experimental setup is similar to experiments that demonstrated a phenomenon termed coherence masking protection (CMP; Gordon, 1997aGordon, ,b, 2000Tarr and Nittrouer, 2011;Nittrouer and Tarr, 2011). In those experiments, a masked LF target signal was presented that was either a single tone (Gordon, 2000), a narrowband noise (Gordon, 1997b), or a low-pass filtered synthesized vowel (Gordon, 1997a;Nittrouer and Tarr, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These basic conditions were compared with conditions in which an additional "cosignal" was presented in higher frequency regions. This cosignal was either a high-pass filtered synthesized vowel (Gordon, 1997a(Gordon, ,b, 2000Nittrouer and Tarr, 2011), a complex tone (Gordon, 2000), or a noise band (Gordon, 2000(Gordon, , 1997b. If the cosignals were presented with the same onand offset as the target signal, the identification thresholds were found to be 3-4 dB lower than in conditions without a cosignal or with a temporally separated cosignal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation